2023
DOI: 10.3389/fmicb.2023.1122184
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analyses of a microbial assemblage in a subglacial lake beneath the Vatnajökull ice cap, Iceland

Abstract: Skaftárkatlar are two subglacial lakes located beneath the Vatnajökull ice cap in Iceland associated with geothermal and volcanic activity. Previous studies of these lakes with ribosomal gene (16S rDNA) tag sequencing revealed a limited diversity of bacteria adapted to cold, dark, and nutrient-poor waters. In this study, we present analyses of metagenomes from the lake which give new insights into its microbial ecology. Analyses of the 16S rDNA genes in the metagenomes confirmed the existence of a low-diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…For instance, Sphingomonas and Shinella have been reported as genera involved in nitrogen fixation (Alok et al, 2020 ; Bizjak et al, 2023 ), phosphate fixation (Asaf et al, 2020 ; Jin et al, 2020 ; Liu et al, 2019 ), carbohydrate metabolism (Anderson & Wood, 1969 ), and photosynthesis (Kopejtka et al, 2021 ; Lu et al, 2022 ). Furthermore, while Pedobacter is a less studied genus, it has been associated with nitrogen fixation and phosphate fixation (Liang et al, 2022 ; Vannier et al, 2023 ); and Parachlorella and the bacterial genus Sphingopyxis are recognized for their ability to participate in photosynthesis (Kopejtka et al, 2021 ; Sharma et al, 2021 ; Vello et al, 2018 ). Several studies, including those by Dueholm et al ( 2022 ) and Wu et al ( 2019 ), have demonstrated a connection between taxonomy and function within wastewater microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sphingomonas and Shinella have been reported as genera involved in nitrogen fixation (Alok et al, 2020 ; Bizjak et al, 2023 ), phosphate fixation (Asaf et al, 2020 ; Jin et al, 2020 ; Liu et al, 2019 ), carbohydrate metabolism (Anderson & Wood, 1969 ), and photosynthesis (Kopejtka et al, 2021 ; Lu et al, 2022 ). Furthermore, while Pedobacter is a less studied genus, it has been associated with nitrogen fixation and phosphate fixation (Liang et al, 2022 ; Vannier et al, 2023 ); and Parachlorella and the bacterial genus Sphingopyxis are recognized for their ability to participate in photosynthesis (Kopejtka et al, 2021 ; Sharma et al, 2021 ; Vello et al, 2018 ). Several studies, including those by Dueholm et al ( 2022 ) and Wu et al ( 2019 ), have demonstrated a connection between taxonomy and function within wastewater microbial communities.…”
Section: Discussionmentioning
confidence: 99%